Bacteriophage based diagnostics for on-farm bovine mastitis testing - Bates, Kristin (My University, 2025)
Bovine mastitis remains one of the most costly and persistent diseases in the global dairy industry, causing annual losses of up to 32 billion USD through reduced milk yield, treatment costs, and premature culling. Current diagnostic tools – such as somatic cell counts, microbial culture, and PCR – are hindered by slow turnaround times, high costs, and technical demands, leading many producers to default to broad antibiotic use. This practice fuels antimicrobial resistance and limits targeted disease control. Bacteriophage-based diagnostics offer a promising alternative. Phages, viruses that specifically infect bacteria, provide highly selective detection of mastitis-causing pathogens such as Staphylococcus aureus, Streptococcus uberis, and Escherichia coli. Reporter phages genetically engineered to express measurable signals upon infection can deliver rapid, pathogen-specific results within minutes. Lyophilization enhances reagent stability, while colorimetric reporter systems enable simple, visual interpretation suitable for on-farm use. Beyond mastitis, phage technologies are already established and applied in food processing as antimicrobial washes to reduce Listeria monocytogenes, Salmonella spp., and E. coli O157:H7 contamination. Extending this proven safety record to diagnostic applications could improve surveillance throughout the dairy supply chain. By combining precision, speed, and field applicability, bacteriophage diagnostics represent a practical and sustainable advancement in veterinary and food safety microbiology. Continued development of multiplex assays, field validation, and regulatory frameworks will be critical for translating this technology into routine farm and processing practices.
Keywords: Reporter bacteriophages; Bovine mastitis; Infectious disease; Diagnostics; Field testing; Point-of-care testing